Asymmetrical nine-level hybrid multilevel inverter design and analysis for electric vehicle applications - Ratnaiah, Gerri; Ganesan, Ramya (International Journal of Applied Power Engineering (IJAPE), 2025)
A novel type of single-phase hybrid multilevel inverter (HMLI) is proposed in this paper. A hybrid system is made up of a multilevel inverter coupled to an H-bridge unit and which can generate nine-level output. To synthesize an output voltage waveform with nine steps, this setup uses merely seven power switches, two diodes, and two DC supplies. A greater number of steps were achieved in output voltage through suggested circuit with a smaller number of components than other existing multilevel inverter (MLI) topologies. A finer output waveform that is closer to a sinusoidal shape is produced with less total harmonic distortion (THD) because of the greater number of steps in the output voltage. Furthermore, it prolongs the switches' lifetime and lowers the voltage stress across them, increasing reliability. In addition, the system produces fewer switches than necessary, resulting in lower power losses and increased efficiency. This guarantees the suggested system's small size and inexpensive cost. A comparison between the suggested topology and the most current MLI topologies has been conducted to highlight the key components of the proposed topology. The suggested topology has been controlled using three distinct controlling schemes are phase disposition-pulse width modulation (PD-PWM), phase opposition disposition-PWM (POD-PWM), and alternative phase opposition disposition-PWM (APOD-PWM).